THE EFFECT OF THE WOODS MODEL ON LEARNING THE SKILLS OF HANDLING AND SUPPRESSION IN FOOTBALL FOR FEMALE STUDENTS - Dr. Muhannad Mohammad Kareem (Journal Park Publishing, 2024)
The multiplicity of teaching methods, methods and teaching models contributed to delivering correct and clear information to the learner and developing their ability to perform skills. The method used and the Woods model aim to achieve learning among the learners. Hence comes the importance of research in developing the level of skill performance of learners in the game of football, and the objectives of the research are to identify On the effect of the method followed and the Woods model in learning the skills of handling and suppression in football for female students, and knowing the difference between the method followed and the Woods model in post-tests, and the extent of the development achieved by the experimental group that worked according to the Woods model. The research sample is first-year female students in the College of Physical Education and Sports Sciences at the University. thi Qar: As for the conclusions, the method used and the Woods model in the educational units had a major role in developing the level and performance of the female students, and the Woods model had a greater role than the method followed in developing the skill performance in the first stage for the female students in the first stage. As for the recommendations, the most important of them was the use of the educational curriculum used in accordance with The Woods model, which had the greatest role in improving and developing the skill performance of first-year female students in the College of Physical Education and Sports Sciences, and the necessity of urging professors and workers in the academic field to use modern teaching models, methods, and methods and use them in other sporting events.
Keywords: woods Model, on learning the skills of handling and suppression, football.